1995
DOI: 10.1037/0735-7028.26.6.608
|View full text |Cite
|
Sign up to set email alerts
|

Do Tarasoff principles apply in AIDS-related psychotherapy? Ethical decision making and the role of therapist homophobia and perceived client dangerousness.

Abstract: The present research assessed the relationship between therapists' beliefs and ethical decision making when working with clients who are HIV positive and who refuse to warn sexual partners or use safe sex practices. The sample consisted of licensed psychologists in Florida. Results demonstrated a significant relationship between homophobia and likelihood of breaching confidentiality. In addition, scenarios depicting highly dangerous clients yielded higher breach scores than scenarios depicting less dangerous c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
45
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(48 citation statements)
references
References 31 publications
3
45
0
Order By: Relevance
“…In accordance with Anderson's method, [18][19][20] the data were analysed, at the group level (lay people, psychologists and medical doctors), by performing analyses of variance and by constructing graphs (with Statistica 5.0). The design of the analysis of variance was participant's age 6 sex 6 severity of the disease 6 time taken 6 intent to inform 6 protective behaviour 6 expert, 2626262636262.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In accordance with Anderson's method, [18][19][20] the data were analysed, at the group level (lay people, psychologists and medical doctors), by performing analyses of variance and by constructing graphs (with Statistica 5.0). The design of the analysis of variance was participant's age 6 sex 6 severity of the disease 6 time taken 6 intent to inform 6 protective behaviour 6 expert, 2626262636262.…”
Section: Discussionmentioning
confidence: 99%
“…In the US, mental health professionals' assessments of the acceptability of breaching confidentiality varied in accordance with the principle of the Tarasoff decisions. [16][17][18][19][20][21][22] In contrast, in France, Moatti and colleagues 23 found that, in accordance with the Ordre des Médecins, general practitioners were in favour of maintaining confidentiality when patients had not consented to having their medical information disclosed, except when the information was to be communicated to another healthcare professional. The attitude of the general public in the US, the UK and France about breaching patient confidentiality have been little studied.…”
mentioning
confidence: 99%
“…US research findings suggest that mental health professionals have become more likely to breach confidentiality in the years between 1978 and 1993 (Rosenhan, Teitelbaum, Teitelbaum, & Davidson, 1993). Relevant criteria for considering whether to disclose information included the kind of risk (Linden thai & Thomas, 1980), the degree of dangerousness (Totten, Lamb, & Reeder, 1990), the identifiability of the victims (Totten et a!., 1990), the imminence of danger (McGuire, Nieri, Abbott, Sheridan, & Fisher, 1995), and clinical experience (Botkin & Nietzel, 1987). Mulligan and Braunack-Mayer (2004) stressed the importance of providing confidentiality in health services because it protects patients from harm, supports their access to health care and produces better health outcomes.…”
Section: Examining Mental Health Professionals) Perceptions Of Confidmentioning
confidence: 99%
“…Differential attitudinal bias toward homosexual PWAs has recently been reported by McGuire, Nieri, Abbott, Sheridan, and Fisher (1995) and Totten, Lamb, and Reeder (1990). Totten et al found that a sample of professional psychologists was more likely to breach confidentiality in a therapy relationship with homosexual and prostitute clients than with bisexual or intravenous drug users all described as not using safer sex practices.…”
Section: Attitudes Toward Pwasmentioning
confidence: 99%